2021
DOI: 10.1016/j.peptides.2021.170583
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic proteins for COVID-19 diagnostics

Abstract: There is an urgent need for inexpensive, rapid and specific antigen-based assays to test for vaccine efficacy and detect infection with SARS-CoV-2 and its variants. We have identified a small, synthetic protein (JS7), representing a region of maximum variability within the receptor binding domain (RBD), which binds antibodies in sera from nine patients with PCR-verified COVID-19 of varying severity. Antibodies binding to either JS7 or the SARS-CoV-2 recombinant RBD, as well as those that disrupt binding betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…The N-terminal domain (NTD) and the r eceptor b inding d omain (RBD) of the S1 protein are important areas for immune recognition and receptor binding 37 . The RBD is both a target for vaccine 38 and diagnostic 39 design. The helical S2 subunit undergoes large conformational changes during the fusion process.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal domain (NTD) and the r eceptor b inding d omain (RBD) of the S1 protein are important areas for immune recognition and receptor binding 37 . The RBD is both a target for vaccine 38 and diagnostic 39 design. The helical S2 subunit undergoes large conformational changes during the fusion process.…”
Section: Resultsmentioning
confidence: 99%
“…Polyclonal antibodies can have overlapping binding sites even to the same peptide epitope [71, 72] and may recognize multiple similar epitopes. For example, in other experiments, we showed that polyclonal antibodies from sera of SARS-CoV-2-infected patients recognize the spike protein of the SARS-2003 virus, despite <80% sequence identity [73]. In the continuation of this alphavirus work, we will analyze the epitope specificity of the antibody ensemble produced in response to our antigens, with the goal of elevating the protective effect of the promiscuous immunogens to that of the species-specific ones against each AV.…”
Section: Discussionmentioning
confidence: 99%
“…For β-COVs the evolutionary path is still debated and the zoonotic origin of the SARS-CoV-2 pandemic is still being investigated. However, most observations indicate that CoVs can move from one species to another, as for example from camels to man (for MERS) and from human to mink and vice versa for SARS-CoV-2 59 , emphasizing the need for antigen based testing for animals that may be asymptomatic carriers 60 Our β-CoV PD-Graph (Figure 4) is consistent with those observations, separating the diverse strains mainly according to their receptor types and not to host types.…”
Section: Discussionmentioning
confidence: 99%